2016
DOI: 10.1016/j.ajpath.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Muscular Dystrophy from Loss of Dysferlin Is Accompanied by Impaired Annexin A6 Translocation after Sarcolemmal Disruption

Abstract: Dysferlin is a membrane-associated protein implicated in membrane resealing; loss of dysferlin leads to muscular dystrophy. We examined the same loss-of-function Dysf mutation in two different mouse strains, 129T2/SvEmsJ (Dysf 129 ) and C57BL/6J (Dysf B6 ). Although there are many genetic differences between these two strains, we focused on polymorphisms in Anxa6 because these variants were previously associated with modifying a pathologically distinct form of muscular dystrophy and increased the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…5e7 Dysferlin is a membrane-associated protein, composed of multiple C2 domains, some of which bind phospholipids in the presence of Ca 2þ . 8 LGMD 2C arises from disruption of g-sarcoglycan, a dystrophin-associated protein, and is accompanied by a similar sarcolemmal fragility, as seen in dystrophin-deficient muscle. 9,10 LGMD 2B and 2C are effectively modeled in Dysferlin-null (Dysf-null ) and Sgcgnull mice, respectively, recapitulating many of the same histopathological features seen in human LGMD 2B and 2C.…”
mentioning
confidence: 99%
“…5e7 Dysferlin is a membrane-associated protein, composed of multiple C2 domains, some of which bind phospholipids in the presence of Ca 2þ . 8 LGMD 2C arises from disruption of g-sarcoglycan, a dystrophin-associated protein, and is accompanied by a similar sarcolemmal fragility, as seen in dystrophin-deficient muscle. 9,10 LGMD 2B and 2C are effectively modeled in Dysferlin-null (Dysf-null ) and Sgcgnull mice, respectively, recapitulating many of the same histopathological features seen in human LGMD 2B and 2C.…”
mentioning
confidence: 99%
“…Notably, GC steroid treatment in dystrophic muscle upregulated many genes encoding proteins implicated in muscle repair (16); thus, the effect of GC steroids on recovery from injury is not just limited to annexin gene expression. Transcriptome analysis showed that genes including caveolin 3 (Cav3), myoferlin (Myof), dysferlin (Dysf), and Trim72 (encoding MG53) were all increased (19,44,45). More refined studies are needed to shed light on whether transcriptional regulation of those genes is directly stimulated by GCs or is an indirect effect of enhanced muscle repair.…”
Section: Resultsmentioning
confidence: 99%
“…We visualized muscle membrane repair in real time using high-resolution microscopy (16,19). In this assay, a laser was used to disrupt the myofiber sarcolemma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysferlin's role in muscle membrane repair was first observed utilizing laser-ablation to induce membrane injury [16]. Dysferlin-null myofibers reseal membrane disruptions much more slowly than normal myofibers, illustrated by an increase in fluorescent FM 1-43 dye uptake after sarcolemmal disruption [16,31]. Immunofluorescence microscopy was used to demonstrate dysferlin's recruitment to the site of membrane insult [16].…”
Section: Introductionmentioning
confidence: 99%